2017
DOI: 10.1002/brb3.708
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral and physiological effects of high‐fat diet and alcohol consumption: Sex differences in C57BL6/J mice

Abstract: Background and ObjectiveAnimal studies can be a great tool to investigate sex differences in a variety of different ways, including behavioral and physiological responses to drug treatments and different “lifestyle variables” such as diets. Consumption of both high‐fat diets and alcohol is known to affect anxiety behaviors and overall health. This project investigated how high‐fat diet and alcohol access and its combination affected the behavior and physiology of male and female C57BL/6J mice.MethodMice were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 83 publications
14
36
0
Order By: Relevance
“…Interestingly, the behavior differences described here were only exhibited by male mice, which also mirrors some human (Alastalo et al, 2013; de Kloet et al, 2005) and animal studies (Arp et al, 2016; Gelineau et al, 2017; Maniam et al, 2010; Naninck et al, 2015). Alastalo et al (2013) have reported that temporarily childhood parental separation during World War II increased the risk for impaired physical and psychosocial functioning in adult men but not in adult women.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, the behavior differences described here were only exhibited by male mice, which also mirrors some human (Alastalo et al, 2013; de Kloet et al, 2005) and animal studies (Arp et al, 2016; Gelineau et al, 2017; Maniam et al, 2010; Naninck et al, 2015). Alastalo et al (2013) have reported that temporarily childhood parental separation during World War II increased the risk for impaired physical and psychosocial functioning in adult men but not in adult women.…”
Section: Discussionsupporting
confidence: 85%
“…Naninck et al (2015) showed that limited nesting and bedding material from postnatal day 2–9 impaired cognitive functions in hippocampus‐dependent tasks more prominently in male adult mice. Furthermore, high‐fat diet exposure decreases activity in open field test in adult male but not in female mice (Gelineau et al, 2017). Similarly, in current study, we found that both the effects of AME‐WD on learning and memory and the effects of postweaning WD on depression‐like behavior were only apparent in males.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, mice maintained on a HFD for 8 weeks showed strong anxiety-like behaviors, evidenced by a significant reduction in total distance traveled (m), the number of entries into the center zone in the OFT, and open arm time spent (s) and distance traveled (m) in the EPM test. A consistent study reported that HFD mice traveled less, and without differences in center preference in OFT and where increased anxiety-like behaviors were present (Gelineau et al, 2017). In our preliminary data, GORZ dissolved in AIN-93M standard food did not show any anxiety or anxiolytic-like effects in a behavioral test; this suggests GORZ is an ideal functional food, as it indicated a protective effect to HFD-induced abnormal behavior, without any effect on normal behavior.…”
Section: Chronic High-fat Diet-induced Anxiety-like Behaviors Can Potsupporting
confidence: 65%
“…One chamber had black walls covered by the lid, and the other had white walls with a 60 W light bulb located 30 cm above the chamber. For the experiment, each mouse was placed in the light chamber and could explore the two chambers for 5 min as described by others [54][55][56]. The following parameters were hand scored: i) latency to enter the dark chamber (sec), ii) latency to re-enter the light chamber (sec), iii) total time spent in the light chamber (sec), and iv) number of crossings/transitions between the two chambers (n).…”
Section: Light-dark Box (Ldb)mentioning
confidence: 99%